The linkage between knowledge management practices and company performance: Empirical evidence - Nausheen Syed; Lin Xiaoyan (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: This study explores the linkage between Knowledge management practices and company performance. Keeping in view the theoretical and empirical importance, the present study examines the predicting linkage of Knowledge management practices (sharing of best practices and building of consistent process, continues employee learning, effective management of knowledge, innovative culture development, and management of core competencies) with company performance. Methodology: The study was carried out on purposively selected sample of 412 employees at different managerial positions. They were administered questionnaires including Knowledge Management Practices and company performance. Data was operated by using SPSS version 20.Correlation and regression analysis was done to establish the relationship between various Knowledge management practices and company performance. Findings: Results of this study illustrated that all selected Knowledge management were positively related to company performance. Based on the findings, and management of core competencies was the strongest predictor of company performance, followed by innovative culture development, effective management of knowledge and sharing of best practices and building of consistent process, continues employee learning. Research limitations/implications: The paper focuses on examining the perceptual impacts of Knowledge management (KM) practices on company performance. The interpretation of results should be taken with caution.Value: The aim of this research is to investigate the relationship between Knowledge management and company performance, study the importance of Knowledge management as a source of sustainable competitive advantages for companies and to investigate how the introduction of Knowledge management practices facilitates company performance to improve. The practices that have a more positive influence on company performance are also discussed.
Keywords: 650; Knowledge management practices; Company performance; Pakistan; Innovative culture; Core competencies